In Silico Molecular Docking and ADMET Evaluation of Active Compounds from Acalypha indica L. Against the HER2 Breast Cancer Target - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Breast cancer is one of the leading causes of cancer-related mortality in women worldwide, and overexpression of human epidermal growth factor receptor 2 (HER2) is associated with aggressive tumor progression, poor prognosis, and treatment resistance. Natural compounds are increasingly explored as safer anticancer candidates due to their structural diversity and lower toxicity profiles. Acalypha indica L., a traditional medicinal plant widely used in Asia, contains numerous phytochemicals with reported antioxidant and cytotoxic activities. This study investigates the binding affinity and pharmacokinetic potential of major A. indica phytochemicals against HER2 using in silico molecular docking and ADMET predictions. Twelve bioactive compounds were selected: quercetin, kaempferol, luteolin, rutin, isoquercitrin, caffeic acid, ferulic acid, esculetin, lupeol, beta-sitosterol, stigmasterol, and acalyphin. Docking was performed using AutoDock Vina against HER2 (PDB ID: 3PP0). Kaempferol (-10.2 kcal/mol), quercetin (-9.8 kcal/mol), and luteolin (-9.3 kcal/mol) showed the highest affinity, interacting strongly with key residues within the HER2 ATP-binding pocket. ADMET analysis indicated that kaempferol, quercetin, and luteolin possessed favorable oral bioavailability and safety characteristics. These findings suggest that A. indica contains promising HER2-targeting phytochemicals that warrant further investigation through in vitro and in vivo studies.